EPISTEMOLOGICAL VIEWS OF ISLAMIC EDUCATION PHILOSOPHY AS A ISLAMIC EDUCATION BASIS - Haris Zubaidillah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2018)
This paper briefly discusses one of the foundations of Islamic education, the epistemological view of Islamic education philosophy. Islamic education as an effort in shaping humanity and civilization must have a firm foundation upon which all activities are connected or propped up. In terms of epistemological, the foundation of Islamic education is the epistemological philosophy of Islamic education sourced from the Qur'an and As-Sunnah as the primary source, as well as the Ijtihad and the intellect that became the branch (furu') of the development of these two primary sources. So that Islamic education really serves as a medium of influencing others toward a better direction in order to live better in accordance with the teachings of Islam and obey all that is ordered and away from all the banned with the awareness of human beings are firmly planted with the scientific aspect so that the result is not just obedient blindness but scholarly servitude, all done within the scope of God's rule. In the end the foundation of education itself is none other than the source of the teachings of Islam that is Al Quran and As-Sunnah.